PENCEGAHAN PENYEBARAN COVID-19 PADA PENDERITA KOMORBID DENGAN PROGRAM PRAKTIK MENCUCI TANGAN DENGAN BENAR - Wilda Fauzia; Julvainda Eka Priya Utama; Fhandy Aldy Mandaty (LPPM STIKES Muhammadiyah Kendal, 2022)
The spread of corona virus infections is increasing, especially in comorbid patients, but there has been no improvement in the practice of implementing health protocols such as washing hands properly. Tangan Bersih Bebas Korona (TASIH ANA) is a program to increase public awareness about the importance of hand hygiene. This study aims to determine the effect of the hand washing program on the practice of washing hands properly in comorbid patients. This study used a quasi-experimental approach with a one group pre-test post-test design approach. The sample of this research were 32 respondents with comorbid with total sampling technique. Analysis of the data used was descriptive statistical analysis and Wilcoxon test. The results showed that there was an effect of the hand washing program on the practice of washing hands properly (p= 0.000 < 0.05). The TASIH ANA program is an effective practice-based health promotion in improving the practice of washing hands properly in preventing the spread of COVID-19 in the community